Analysis Of Cisanggarung River Flood In Sidaresmi Village, Pabedilan District, Cirebon Regency Using Hec-Ras Software - Prasetyo, Dimas; Fachrie Algadry, Mochamad Aby; Nurdiyanto, Nurdiyanto (Jurnal Locus Penelitian dan Pengabdian, 2024)
The eastern part of Cirebon Regency is an area that is prone to flooding because it is included in the Cisanggarung Watershed (DAS). The Cisanggarung watershed area has a high level of flood vulnerability, with the flood-prone area reaching around 3,479 hectares. This study aims to analyze flooding in Sidaresmi Village by employing the HSS Nakayasu method to calculate the flood discharge levels. This approach facilitates the estimation of peak flood discharges for a range of return periods, including Q2 or 2-year, Q5 or 5-year, Q10 or 10-year, Q25 or 25-year, Q-50 or 50-year, Q100 or 100-year. Subsequently, these discharge values are utilized in flood modeling conducted with HEC-RAS software. The modeling results using HEC-RAS software show that the Cisanggarung River in Sidaresmi Village does not have sufficient capacity to accommodate the flood discharge that occurs. With flood discharges exceeding the river's capacity, the risk of overflowing water becomes very high, which can result in flooding in surrounding areas. These findings highlight the importance of mitigation measures, such as river infrastructure improvements, to reduce the impact of flooding in the area.